Reading the Other Side of the Story: Ominous Voice and the Sociocultural and Political Implications of Luis Spota's Murieron a mitad del río - Francisco Manzo-Robledo (Studies in 20th & 21st Century Literature, 2001)
It is always contoversial to proclaim a literary work, at face value, as a sociocultural study of a particular society. It is even more controversial when one deals with a hybrid work, combining factors from two completely distinct societies. Yet, there are some literary works that seem to call for exactly this type of analysis, presenting a range of ideas which in retrospect reveal origins of significant sociocultural trends. Such is the case of Luis Spota's Murieron a mitad del río (1948). This novel presents a panorama of ancestral problems in the life of thousands of immigrants and inhabitants of the Mexican-U.S. border region trying to achieve a "better life for them and their children," yet forced to live in social limbo. These individuals reside neither entirely in Mexico nor in the United States, but in a place where the existence of tensions started with the competition for jobs amongst the "already in" and the "newly arrived" (regardless of the legal status) augmenting the differences created by a new environment. Although only implicitly present in the novel, some of these problems are approached from a legal point of view creating, contrary to their intended purpose, a better means for the selection of immigrant manual labor. Although not in the novel, a case in point would be the new "walls of ignominy" along the Tijuana-San Diego crossing, where undocumented migration has shifted east toward Calexico and other parts of the Arizona desert. Since conditions to cross the border there illegally are more rigorous, only the young and strong dare to do it. This essay examines the manner Spota uses to expose his particularly "urban" point of view and a set of social problems, from a cultural theory point of analysis. It demonstates that Murieron a mitad del río presents a microcosm of the issue and in a way, predicts some of the main dilemmas that both countries will encounter through the years. Thus, Spota becomes a visionary, dealing in his own idiosyncratic manner with a still compelling topic.
Keywords: sociocultural; political; Luis Spota; Mureron a mitad del río; north; el norte; border narratives; immigrants; Mexican-U.S. border; border citizens; identity; nationalism; conflict; border conflict; in between